MINIMASI TINGKAT ERROR MUTASI ANTARA DATA AKTUAL DENGAN MAXIMO MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DI PT. INDONESIA POWER UBP SEMARANG - Nur Riana Fajarwati; Harwati Harwati (Teknoin, 2014)
Activity out of the goods happen almost everyday in the warehouse PT. Indonesia Power UBP Semarang. All activities that occur out of the goods in the warehouse must be recorded manually (Actual Data) in paper hanging and should be tailored to maximo which is a control system of PT. Indonesia Power. Based on the observations made, it appears that the common difference (error) between the amount of goods are recorded manually on a hanging card with recording stuff in maximo. Mutations actual data contained on the card suspension should always be updated with the existing data in order to avoid errors maximo between items with the notes of. Analytical Hierarchy Process (AHP) is a technique to help resolve problems that are complex. The use of AHP technique is applied to minimize the error rate of mutation between the actual data with maximo. With alternative proposals overtime, relayout workspace, adding employees and training employees who assessed based on criteria obtained is the cost, complexity, time, level of risk and the effectiveness of the proposed result that the best alternative is the provision of training to employees in PT. Indonesia Power UBP Semarang.